2010
DOI: 10.1029/2010gl045171
|View full text |Cite
|
Sign up to set email alerts
|

Lifting potential of solar‐heated aerosol layers

Abstract: Absorption of shortwave solar radiation can potentially heat aerosol layers and create buoyancy that can result in the ascent of the aerosol layer over several kilometres altitude within 24–48 hours. Such heating is seasonally dependent with the summer pole region producing the largest lifting in solstice because aerosol layers are exposed to sunshine for close to 24 hours a day. The smaller the Angstrøm parameter, the larger the lifting potential. An important enhancement to lifting is the diffuse illuminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 14 publications
(14 reference statements)
2
56
0
Order By: Relevance
“…Strong bushfires, very high temperatures, low winds, and thunderstorm evolution on 7 February, 2009, ("Black Saturday") triggered the lifting of enormous amounts of smoke towards the upper troposphere from where the smoke layers ascended by the self-lifting mechanism to a height of 15-20 km (Boers et al, 2010;de Laat et al, 2012). Similar maximum 532 nm AEC and AOT values as measured over central Europe on 21-22 August 2017, were observed with the CALIPSO lidar in the lower stratosphere over the South Pacific east of Australia at heights above the tropopause and below 20 km a few days after 7 February, 2009, (de Laat et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong bushfires, very high temperatures, low winds, and thunderstorm evolution on 7 February, 2009, ("Black Saturday") triggered the lifting of enormous amounts of smoke towards the upper troposphere from where the smoke layers ascended by the self-lifting mechanism to a height of 15-20 km (Boers et al, 2010;de Laat et al, 2012). Similar maximum 532 nm AEC and AOT values as measured over central Europe on 21-22 August 2017, were observed with the CALIPSO lidar in the lower stratosphere over the South Pacific east of Australia at heights above the tropopause and below 20 km a few days after 7 February, 2009, (de Laat et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Khaykin et al (2018) found that the smoke plumes ascended rapidly over the first few days following their injection into the upper troposphere with a rate of 2-3 km per day. This cross isentropic ascent was caused by radiative heating of smoke aerosols (Boers et al, 2010). The second aspect is that the wind velocity decreases with height from the tropopause to an altitude of 16 km (GDAS, 2018) as well as from the tropopause to the middle troposphere (5 km height).…”
Section: Satellite-derived Products: Modis and Omi Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Or in other words, rather than being advected passively with the prevailing winds, absorbing aerosols may actually have a direct impact on their own vertical transport. The framework for this idea dates back to the work of Malone et al [1986] and Radke et al [1990] and was revived by Boers et al [2010]. According to calculations by Boers et al [2010], optically thick layers of absorbing aerosols can be lifted from the lower troposphere to the (extratropical) tropopause due to diabatic heating within 3–4 days, the so‐called “self‐lofting” mechanism of Radke et al [1990].…”
Section: Introductionmentioning
confidence: 99%
“…Plumes containing soot particles also change the local atmospheric stability due to the ability to heat the ambient air by absorbing the solar radiation. Hence, elevated biomass burning layers have the potential of additional lifting, increasing persistence and thus longer lifetimes in the free troposphere (Boers et al, 2010). At the top of the atmosphere semi-direct radiative effects can differ in sign depending on the location of the biomass burning plumes and their underlying surface, that is, if they are located above land (positive semi direct radiative effect) or ocean (negative semi direct radiative effect) (Sakaeda et al, 2011).…”
Section: Transport Of Smoke Plumes Downwind From the Source Regionmentioning
confidence: 99%